A vigilância socioassistencial como função da Política de Assistência Social: um estudo da gestão municipal na microrregião de Itapecerica da Serra/SP - Ribeiro, Kassia Siqueira (2015)
As general objective, this master thesis aims at knowing settings of Social Assistance Surveillance, responsible for the process of production, systematization, analysis, and territorialized information spread in the field of Municipal Social Assistance Policy. Specific objectives were 1) to understand Sistema Único de Assistência Social/Suas workers perceptions of operational and conceptual aspects regarding the Social Assistance Surveillance; 2) to analyse if social assistance decision-making processes take territorialized information into account; and 3) to know processes, tensions, gaps and potentialities. Considering that Social Assistance Surveillance is not fully implemented in all States and Municipalities, along with its production in an initial stage, it is important to reinforce the university s social role to unveil poorly explored facts in order to support public policies improvements. The main hypothesis is that Social Assistance Surveillance implementation is condition for strengthening public and preventive aspects of Sistema Único de Assistência Social/Suas. It was adopted a qualitative approach to incorporate all knowledge produced throughout this research process, as well as literature and documentary research to assure technical support. Interviewing and observational techniques were applied to apprehend the daily routines of the municipal public management.05 interviews were conducted, involving 03 social assistance network professionals (Cras and Creas), and 02 municipal public managers. Results showed that difficulties of implementing Social Assistance Surveillance are related to work management, as reduced teams are less capable of conducting surveillance in the territories. Moreover, information processing is largely manual, hindering a better exploitation of all produced information, which is considered neither in planning public policies, nor in working process orientation for technical teams. Advances refer to the concern about developing technical instruments, standardizing, recording and storing information in order to create strategic and accurate data for future use, such as socioterritorial diagnostics and Municipal Social Assistance Plan. The teams also recognize the need to implement Social Assistance Surveillance urgently. Although the municipal public management and the social assistance network have been carrying out these activities, it is important to define workflows concerning data collection and information use to enhance Social Assistance Policy